Menilai Keterbacaan Buku Cerita Dwibahasa Anak: Melibatkan Guru dan Siswa untuk Mendorong Minat Baca di Balai Bahasa Provinsi Riau - Sukenti, Desi; Alber, Alber; Tambak, Syahraini; Hidayatunnur, Hidayatunnur; Latif, Latif; Devi, Sylvia Pratama (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
This study was motivated by children's low interest in reading storybooks available at school. Although the books presented are interesting and good, they do not offer many bilingual storybooks to introduce local culture. This study aims to describe the readability level of bilingual children's storybooks by involving teachers and students to encourage their interest in reading. This study uses a descriptive-quantitative method. The data collection techniques used are questionnaires and documentation. The sample used consisted of 65 respondents, comprising 40 teachers and 25 students. The results of this study indicate that the readability level of bilingual children's storybooks from the teachers' perspective can be described in four aspects: the readability of bilingual storybooks in terms of material (80.34%); presentation (80.87%); graphics (77.79%); and language (72.87%). Overall, the readability level of storybooks from the perception of B-2 level students was in the Very Good category. This means that the readability level of storybooks is easy for students to understand. Based on the findings of this study, the readability level of bilingual storybooks is suitable for use by students to learn about the regional languages of various ethnic groups, thereby developing students' literacy skills through a love of reading storybooks.